PENGARUH RETRIBUSI OBJEK WISATA, JUMLAH WISATAWAN, DAN PAJAK HIBURAN TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN KARANGANYAR - Sri Indriyani, Suprihatmi Sri Wardiningsih & Setyaningsih Sri Utami (Universitas Slamet Riyadi, 2018)
This study aims to analyze the retribution of tourist attractions, the number oftourists and entertainment taxes to the original income of karanganyar regency. Thisstudy uses quantitative data and uses secondary data sources. The population of thisresearch is 48 data and sample of this research consist of 48 data from retribution oftourist object, number of tourists, entertainment tax and local revenue. Data analysistechniques use classical assumption test, multiple linear regression, t test, F test andcoefficient of determination. The result of research partially indicate that the retributionof tourist object and the number of tourist tourists have positive but not significant effectto the original income of the region. The entertainment tax has a positive and significanteffect on the local revenue. Simultaneously the retribution of tourist attraction, thenumber of tourists and entertainment tax has a positive and significant effect on the localrevenue.Keywords: local revenue, levy of tourist attraction, number of tourists, entertainment tax